Comparative Evaluation of Psidium guajava Leaf Powder with Injectable Platelet-rich Fibrin and Demineralized Freeze-dried Bone Allograft with Injectable Platelet-rich Fibrin in the Management of Periodontal Intrabony Defects: A Clinicoradiographic Study - Surekha Ramrao Rathod; Palak Abhay Kasliwal; Pranjali Vijaykumar Bawankar; Abhay P. Kolte (Journal of International Clinical Dental Research Organization, 2025)
Background: The current trial aims to evaluate and compare the effects of Psidium guajava leaf powder with injectable platelet-rich fibrin (iPRF) and demineralized freeze-dried bone allograft (DFDBA) with iPRF in the management of periodontal intrabony osseous defects, clinically and radiographically using a cone-beam computed tomography. Methods: Twenty-eight periodontal intrabony defects were involved in this clinical trial. The control group was treated with DFDBA with iPRF, and the test group was treated with P. guajava leaf powder with iPRF. At baseline, 3 months, and 6 months, the gingival index (GI), plaque index (PI), probing pocket depth (PPD), and clinical attachment level (CAL) were assessed, whereas radiographic parameters were assessed at baseline and 6 months. Results: Both the test and control groups showed significant improvements in clinical and radiographic parameters, including a reduction in GI, PI, PPD, and CAL after 3 and 6 months. The test group demonstrated greater CAL gain and better radiographic compared to the control group, though bone fill was similar between both the groups. Conclusion: P. guajava leaf powder with iPRF showed statistically comparable results with DFDBA with iPRF, showing that P. guajava leaf powder can be used for periodontal regeneration.